Boosting oxygen electrocatalytic reactions with Mn3O4/self-growth N-doped carbon nanotubes induced by transition metal cobalt. Issue 21 (15th September 2020) - Lu, Li-Na; Chen, Cheng; Xiao, Kang; Ouyang, Ting; Zhang, Jun; Liu, Zhao-Qing
Abstract : Oxygen electrocatalytic activities in transition-metal atoms and/or heteroatom-doped carbon nanostructures are strongly dependent on their conductivity and electron configurations. Abstract : Oxygen electrocatalytic activities in transition-metal atoms and/or heteroatom-doped carbon nanostructures are strongly dependent on their conductivity and electron configurations. Herein, this study reports Mn3 O4 /self-growth carbon nanotubes induced by a transition metal cobalt hybrid as the efficient bifunctional oxygen electrocatalyst for rechargeable zinc–air batteries. The positive effect posed by the hierarchical structure and heteroatom doping provides an extra electronic state, eventually enhancing the oxygen adsorption and charge transfer during oxygen electrochemical reactions. The assembled rechargeable zinc–air battery achieves a high power density of 128 mW cm −2 and an excellent cycle stability of over 160 h at 5 mA cm −2 . This study provides a feasible approach for designing efficient bifunctional oxygen electrocatalysts for broad applications in the field of energy conversion technology.